The Influence of Gadget Use on Academic Achievement of 2016 Unsyiah Physics Batch - Nur Khairina Hidayatika; Mustafa Mustafa; Tarmizi Tarmizi (Universitas Syiah Kuala, 2019)
In this globalization era, communication tools are very fast examples. Gadgets are a communication tool that has many functions. Where the function is already using the different features. Gadgets considered more complete than other electronics because of its functionality and different. Gadgets examined included laptops and mobile phones. The approach used in this research is the quantitative study. In the approach comes from the students who actively use the gadget in the context lectured. Collection of activity data using questionnaires and student evidence. As for the CPI data analysis and processing used by the product moment correlation coefficient and linear regression simple shapes in which both the data intervals. Based on the analysis of data, a scoreprice r count is larger than a good table for the error of 5% and 1% (0.76 0.345 0.266), so that Ha is accepted and Ho is rejected. The conclusion of this research is there is a positive use of gadgets to force GPA student education physics, 2016. which is expected to help raise the GPA when the use of gadgets is positively.